Chromium coated silicon nitride electron beam exit window. (March 2015) - Manivannan, N.; Balachandran, W.; Ribton, C.; Beleca, R.; Abbod, M.; Cox, M.; Anastasia, P.
Abstract: A Si3 N4 membrane with a thin Cr coating is proposed and demonstrated as an electron beam exit window. On average, 85% electron power transmission efficiency was achieved with a 1 μm thick Si3 N4 membrane coated with 1 μm thick Cr and the membrane sustained a beam current of up to 3  mA at 60 keV electron energy for the continuous operation of 3 min. However, for an uncoated membrane of same thickness, the average electron power transmission efficiency was 71% and the maximum beam current sustained was 800 μA. It was also shown that a one micron thick Si3 N4 square membrane window of 10 mm × 10 mm could withstand a differential pressure of 1.3 bars. Highlights: Chromium coated Si3 N4 thin membrane was proposed as an electron beam exit widow. The device was experimented for low electron energy and high beam current. Finite element method analysis was carried out for thermal profile of the device. Maximum differential pressure across the device was experimentally tested. Metal coating has increased the transmitted beam current by four fold.